2020
DOI: 10.1021/acs.inorgchem.0c00844
|View full text |Cite
|
Sign up to set email alerts
|

pH- and Time-Dependent Release of Phytohormones from Diruthenium Complexes

Abstract: The controlled release of functionally active compounds is important in a variety of applications. Here, we have synthesized, characterized, and studied the magnetic properties of three novel metal−metal-bonded tris(formamidinato) Ru 2 5+ complexes. We have used different auxin-related hormones, indole-3-acetate (IAA), 2,4-dichlorophenoxyacetate (2,4-D), and 1-naphthaleneacetate (NAA), to generate [Ru 2 Cl(μ-DPhF) 3 (μ-IAA)] (RuIAA), [Ru 2 Cl(μ-DPhF) 3 (μ-2,4-D)] (Ru2,4-D), and [Ru 2 Cl(μ-DPhF) 3 (μ-NAA)] (RuN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…1, as well as in other similar complexes. 20,42–44,62–64 A second peak in the mass spectra of compounds 1 and 2 , assigned to the species [M + CH 3 CO] + , is observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, as well as in other similar complexes. 20,42–44,62–64 A second peak in the mass spectra of compounds 1 and 2 , assigned to the species [M + CH 3 CO] + , is observed.…”
Section: Resultsmentioning
confidence: 99%
“…40 Due to the high coordination capacity of the open-paddlewheel complexes, they can interact with nucleic acids, 20 biological macromolecules such as RNA, 41 and can be used as drug carriers. 42 In the case of monosubstituted [Ru 2 Cl(DArF)(O 2 CR) 3 ] compounds, until very recently, 43 only two species had been synthesized and described. 44 To the extent of our knowledge, no further studies in the supramolecular field have been carried out, even when they present three equatorial positions that can be replaced and two axial sites that can work as Lewis acidic sites.…”
Section: Introductionmentioning
confidence: 99%
“…4). 63 The produced complexes [Ru 2 Cl(μ-DPhF) 3 (μ-IAA)], [Ru 2 Cl(μ-DPhF) 3 (μ-2,4-D)], and [Ru 2 Cl(μ-DPhF) 3 (μ-NAA)] were tested for their capability to detach the bound hormone at various pH values, via a very sensitive assay prepared on the basis of Arabidopsis thaliana plants; results demonstrated that the auxin ligands were released more rapidly at acidic and neutral pH than in slightly alkaline media. Indeed, as the auxins were found to be mostly in their anionic forms in solutions, their release from the diruthenium( ii , iii ) scaffold necessitates a protonation step, thus being favored in acidic pH.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…The syntheses and properties of numerous formally mixed-valent diruthenium(II,III) complexes have been reported to date [1][2][3]. The synthesis and reactivity of tetracarboxylatochloridodiruthenium complexes, [Ru 2 Cl(µ-O 2 CR) 4 ] (R = alkyl o aryl), with paddlewheel structure have been intensively studied due to their singular electronic and magnetic properties [4] and their potential applications in several fields as catalysers [5,6], anticancer drugs [7,8], drugs carriers [9] or structural probes of biomolecules [10][11][12]. These complexes are usually obtained by the metathesis reaction of [Ru 2 Cl(µ-O 2 CMe) 4 ] n with an excess of the corresponding carboxylic acid in a refluxing mixture of methanol/water (1:1).…”
Section: Introductionmentioning
confidence: 99%